The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.2337/diab.46.9.1419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Muscarinic Receptor Subtypes in RINm5F Cells by Means of Polymerase Chain Reaction, Subcloning, and DNA Sequencing

Abstract: Carbachol can stimulate insulin release in RINm5F cells by a mechanism that does not involve the elevation of cytosolic free Ca2+ concentrations or the activation of conventional protein kinase Cs (Mol Pharmacol 47:863-870, 1995). Thus, a novel signal transduction pathway links the muscarinic activation of the cells to increased insulin secretion. The question arises as to whether the pathway results from a novel receptor, different from the five established muscarinic receptors, or whether a "normal" receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
4
2
1
Order By: Relevance
“…However, while previous studies reported the expression of additional mAChR subtypes (e.g. M 4 or M 5 ) in islet preparations or in b-cell derived cell lines [19,20], we did not detect M 2 , M 4 or M 5 receptor mRNA in mouse pancreatic islets.…”
Section: The M 3 Machr Mediates Ach-induced Enhancement Of Gsiscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, while previous studies reported the expression of additional mAChR subtypes (e.g. M 4 or M 5 ) in islet preparations or in b-cell derived cell lines [19,20], we did not detect M 2 , M 4 or M 5 receptor mRNA in mouse pancreatic islets.…”
Section: The M 3 Machr Mediates Ach-induced Enhancement Of Gsiscontrasting
confidence: 99%
“…Receptor localization studies suggest that multiple mAChRs (M 1 , M 3 , M 4 and/or M 5 ) are expressed in pancreatic islets/b-cells or b-cell-derived tumour cell lines [18][19][20]. We initially carried out a series of RT-PCR studies to examine which mAChR subtypes are expressed by mouse pancreatic islets.…”
Section: The M 3 Machr Mediates Ach-induced Enhancement Of Gsismentioning
confidence: 99%
“…Similar findings were obtained with rat pancreatic islets (23,25). Whereas previous studies (24,25) reported the expression of additional muscarinic receptor subtypes (M 4 or M 5 ) in islet preparations or in ␤-cellderived cell lines, we did not detect M 2 , M 4 , or M 5 receptor mRNA in mouse pancreatic islets. Because the majority of the cells in rat or mouse islets represent ␤-cells, it is highly likely that both M 1 and M 3 receptors are expressed by the insulin-secreting ␤-cells.…”
Section: Discussioncontrasting
confidence: 30%
“…Molecular cloning studies have revealed the existence of five molecularly distinct muscarinic receptor subtypes (M 1 ϪM 5 ) (22). Receptor localization studies suggest that multiple muscarinic receptors (M 1 , M 3 , M 4 , and M 5 ) are expressed in pancreatic islets/␤-cells or ␤-cellϪderived tumor cell lines (23)(24)(25). However, the M 3 muscarinic receptor appears to be the predominant subtype expressed by pancreatic ␤-cells (4 -6,23-25).…”
mentioning
confidence: 99%
“…104 Additionally, the muscarinic receptor type 3 (M3) appears to be the predominant subtype expressed by pancreatic b-cells. [99][100][101][105][106][107] The role of muscarinic receptors in insulin release is well described in studies performed in M3 receptor-deficient mice (M3 -/-). Specifically, the infusion of the muscarinic agonist oxotremorine in islet cells either failed to stimulate insulin release in M3 receptor-deficient mice (M3 -/-) or was strongly inhibited in islets from M3 +/-mice.…”
Section: Muscarinic Receptors and Glucose Homeostasismentioning
confidence: 99%